PUBLIC PRIVATE PARTNERSHIP IN THE DEVELOPMENT OF PUBLIC TRANSPORTATION IN THE CITY OF SURABAYA - Bayu Priambodo; Agus Widiyarta (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
This study discusses the implementation of public-private partnerships in Surabaya in the development of transportation infrastructure. The Surabaya city government has been exploring the construction of mass transportation in the form of trams since 2010 but until now the construction of the tram has not started. The method in this research is descriptive qualitative where data collection uses literature study and analyzed using the concept of public private partnership. The results of this study indicate that the implementation of public-private partnerships in local governments is less successful. This is because the resources owned are still very limited so that many developments are stopped in the middle of the road. In addition, the implementation of public-private partnerships in developing countries is still using the traditional system. From the outside it uses the new public management but from the inside it still uses the traditional system.